Driving Speed Is Altered by Monocular Neutral Density Filters: The Enright Phenomenon - Andrew Carkeet; Joanne M. Wood; Andrew Robinson; Jonathan J. McCorriston; Nina Pesic; Sarah L. Warlow (2011)
An observer, looking sideways from a moving vehicle, while wearing a neutral density (ND) filter over one eye, can have a distorted perception of speed, known as the Enright phenomenon. The purpose of this study was to determine how the Enright phenomenon influences driving behavior.A geometric model of the Enright phenomenon was developed. Ten young, visually normal, participants (mean age = 25.4 years) were tested on a straight section of a closed driving circuit and instructed to look out of the right side of the vehicle and drive at either 40 km/h or 60 km/h under the following binocular viewing conditions: with a 0.9 ND filter over the left eye (leading eye); 0.9 ND filter over the right eye (trailing eye); 0.9 ND filters over both eyes, and with no filters over either eye. The order of filter conditions was randomized and the speed driven recorded for each condition.Speed judgments did not differ significantly between the two baseline conditions (no filters and both eyes filtered) for either speed tested. For the baseline conditions, when subjects were asked to drive at 60 km/h, they matched this speed well (61 ± 10.2 km/h) but drove significantly faster than requested (51.6 ± 9.4 km/h) when asked to drive at 40 km/h. Subjects significantly exceeded baseline speeds by 8.7 ± 5.0 km/h, when the trailing eye was filtered and traveled slower than baseline speeds by 3.7 ± 4.6 km/h when the leading eye was filtered.This is the first quantitative study demonstrating how the Enright effect can influence perceptions of driving speed and demonstrates that monocular filtering of an eye can significantly impact driving speeds, albeit to a lesser extent than predicted by geometric models of the phenomenon.